Augmented Reality for Endoscopic Sinus Surgery With Surgical Navigation: A Cadaver Study - Citardi, Martin J. (Int Forum Allergy Rhinol, 2015)
INTRODUCTION: Augmented reality (AR) fuses computer-generated images of preoperative imaging data with real-time views of the surgical field. Scopis Hybrid Navigation (Scopis, GmbH, Berlin, Germany) is a surgical navigation system with AR capabilities for endoscopic sinus surgery (ESS). METHODS: Pre-dissection planning was performed with Scopis Hybrid Navigation software followed by ESS dissection on 2 human specimens using conventional ESS instruments. RESULTS: Pre-dissection planning included creating models of relevant frontal recess structures and the frontal sinus outflow pathway on orthogonal CT images. Positions of the optic nerve and internal carotid artery were marked on the CT images. Models and annotations were displayed as an overlay on the endoscopic images during the dissection, which was performed with electromagnetic surgical navigation. The accuracy of the AR images relative to underlying anatomy was better than 1.5 mm. The software's trajectory targeting tool was used to guide instrument placement along the frontal sinus outflow pathway. AR imaging of the optic nerve and internal carotid artery served to mark the positions of these structures during the dissection. CONCLUSIONS: Surgical navigation with AR was easily deployed in this cadaveric model of ESS. This technology builds upon the positive impact of surgical navigation during ESS, particularly during frontal recess surgery. Instrument tracking with this technology facilitates identifying and cannulation of the frontal sinus outflow pathway without dissection of the frontal recess anatomy. AR can also highlight “anti-targets” (i.e., structures to be avoided), such as the optic nerve and internal carotid artery, and thus reduce surgical complications and morbidity.